2023
DOI: 10.1113/ep091162
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of preventive and therapeutic effects of continuous exercise on acute lung injury induced with methotrexate

Mohammad‐Amin Rajizadeh,
Mahdiyeh Haj Hosseini,
Mina Bahrami
et al.

Abstract: Methotrexate (Mtx) is used to treat various diseases, including cancer, arthritis and other rheumatic diseases. However, it induces oxidative stress and pulmonary inflammation by stimulating production of reactive oxygen species and cytokines. Considering the positive effects of physical activity, our goal was to investigate the preventive and therapeutic role of continuous training (CT) on Mtx‐induced lung injury in rats. The rats were divided into five groups of 14 animals: a control group (C); a continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The significant increase in MPO in the brain regions can affect the development of neurodegeneration [ 52 ]. Reduced transcription of GATA3 and absence of MPO in the brains infected with NS80 viruses may be beneficial [ 53 ]. It was recently shown that cognitive, memory, and proinflammatory activities were improved in the Alzheimer’s disease mouse model (5XFAD) after producing bone marrow deficient MPO [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in MPO in the brain regions can affect the development of neurodegeneration [ 52 ]. Reduced transcription of GATA3 and absence of MPO in the brains infected with NS80 viruses may be beneficial [ 53 ]. It was recently shown that cognitive, memory, and proinflammatory activities were improved in the Alzheimer’s disease mouse model (5XFAD) after producing bone marrow deficient MPO [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our prior research, we demonstrated the protective effects of continuous aerobic exercise against methotrexate-induced lung injury [ 25 ]. In this study, our focus was to evaluate the impact of High-Intensity Interval Training (HIIT), characterized by brief periods of intense anaerobic exercise alternated with short recovery periods, on methotrexate-induced lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment was performed without knowledge of the animal groups, ensuring objectivity. The grading of lung injury was based on the evaluation of histological features [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the immune detection step, a Chemi Doc XRS + imaging system (Bio-Rad Company, USA) was utilized. Subsequently, the resulting images were subjected to meticulous analysis employing ImageJ software 49 , 50 . Notably, β-Actin (SANTA CRUZ, sc-47778) served as the designated housekeeping protein 51 , 52 .…”
Section: Methodsmentioning
confidence: 99%